Case report: CAR-T therapy demonstrated safety and efficacy in relapsed/refractory diffuse large B-cell lymphoma patients complicated with hepatitis B-related cirrhosis - Kong, Danqing; Ping, Nana; Zhu, Qian; Zhang, Xiao; Li, Junhong; Zou, Rui; Wu, Depei; Jin, Zhengming; Qu, Changju (Frontiers in Oncology, 2024)
Chimeric antigen receptor T-cell (CAR-T) therapy has demonstrated both efficacy and safety in relapsed/refractory diffuse large B-cell lymphoma (DLBCL) patients infected with hepatitis B virus (HBV). However, its applicability in individuals with liver cirrhosis remains largely unexplored due to the potential for unpredictable complications. Here, we report three cases (P1, P2, and P3) of relapsed/refractory DLBCL with HBV-related cirrhosis treated with CAR-T cell infusion. P1 and P2 received CAR-T cell infusion following a conditioning regimen of fludarabine and cyclophosphamide (FC) for lymphodepletion, while P3 received the SEAM (semustine, etoposide, cytarabine, and melphalan) regimen and autologous stem cell transplantation bridging CAR-T cell infusion. P1 and P2 achieved rapid complete remission (CR), whereas P3 initially exhibited stable disease a month after CAR-T infusion and subsequently achieved CR after local radiation salvage therapy and lenalidomide maintenance. With a median follow-up of 42 months after CAR-T, the progression-free survival rate was 100%. Notably, during follow-up, these patients experienced complications associated with cirrhosis, including endoscopic variceal bleeding, HBV reactivation, or the diagnosis of hepatic malignancy. Our findings suggest that CAR-T therapy is applicable and effective for the treatment of DLBCL patients with HBV-related cirrhosis, albeit necessitating monitoring for potential hepatic complications.